The Development of Response and Interference Inhibition in Children: Evidence from Serious Game Training - Lingyun Wang; Jiajia Li; Fanli Jia; Lin Lian; Lihong Li (MDPI AG, 2024)
A serious game titled "Crossing the Jungle" was developed in this study to train children's inhibition skills using the Stroop task. The effects of inhibitory control on children were tested by a pre-test, post-test, and one-month follow-up test. In the control groups, children were asked to play a commercial game instead. In experiment 1, 48 participants chose either the training or control game voluntarily, whereas, in experiment 2, 44 participants were randomly assigned to either group. In both experiments, children exposed to the serious game demonstrated training effects from the Stroop spatial task and near-transfer effects from the Flanker task. However, transferring effects were not produced by the Go/No-go task. As a result, although the serious game "Crossing the Jungle" does not improve response inhibition, children aged 9 to 12 who play it may benefit from improved interference inhibition abilities. This provides evidence for the mutual independence of interference inhibition and response inhibition in children at this stage.